Pemberdayaan Karang Taruna Desa Bunga-Bunga dalam Menangkal Hoaks terkait COVID-19 - Kurnia Harli; Heriyati Heriyati; Eva Yuliani; Masyita Haerianti; Muhammad Irwan; Irfan Irfan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
During this pandemic, the spreading of hoaxes related to COVID-19 with provocative titles is out of control. Youth organizations as a forum for youth to develop themselves, grow awareness and social responsibility from, for, and by youths were expected to overcome social problems faced by taking an active role in increasing public awareness and vigilance, primarily related to the COVID-19 hoax. Therefore, through this empowerment activity, Desa Bunga-Bunga youth organizations as active internet consumers were expected to increase their ability to think critically in filtering and interpreting information received from the internet and educate others to minimize the existence of hoax-related to COVID-19 in the community. The method of this activity was lecture and discussion of effective communication, hoax, and COVID-19. The participants’ knowledge was assessed by pre-test and post-test. The participants’ understanding of hoax and COVID-19 increased while the communication topic decreased. In conclusion, the participants could sort out hoaxes related to COVID-19.